DEVELOPING CRITICAL THINKING THROUGH VISUAL ARTS EDUCATION AT SECONDARY SCHOOLS - Beknazarova Pokiza Nurillobek qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the role of visual arts education in developing critical thinking skills among secondary school students. Critical thinking is essential for analyzing, evaluating, and interpreting visual information and for making informed artistic decisions. The study explores pedagogical strategies, projectbased learning, interactive methods, and the integration of digital technologies as key approaches for promoting critical thinking. Additionally, it highlights the importance of the teacher’s guidance in facilitating reflective analysis and encouraging independent reasoning in students.